Dramaturgy Study: The Story of “Si Pandir” on The Effectiveness of Village Fund Management - Cahyono, Suham; Sudaryati, Erina; Sawarjuwono, Tjiptohadi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Purpose: The aim of this study was to uncover the intricacies of village fund budget management by offering a comprehensive portrayal of the behaviors exhibited by the key actors involved in village budget management, both in front and behind the scenes. The aim of this study focuses on the workings of the X village fund budget, highlighting the role of third parties in optimizing the utilization of the X village fund budget. Method: A qualitative method with a dramaturgical study approach is used in this study to answer the proposed study proposition Results: The findings indicate that the dynamics observed in the management of the X village fund budget can lead to optimal resource allocation aligned with the village's development objectives and the well-being of its community. This is because the village fund administrators engage in strategic budgetary maneuvers to achieve the utmost efficiency in budget management. The positive impact stemming from the proactive involvement of the village apparatus, colloquially referred to as